Studi Etnografi Virtual Kritik Sosial dalam Konten Kanal Youtube Tekotok terkait Kenaikan Harga Bahan Bakar Minyak di Indonesia - Basli, Muhammad Yassaar; Achmad, Zainal Abidin (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research is entitled "Virtual Ethnographic Study of Social Criticism in the Content of the Tekotok Youtube Channel Regarding the Rise in Indonesian Fuel Prices", which was conducted using qualitative research methods, and the data collected is primary data. The research method used is the virtual ethnographic method used to explore and analyze the virtual culture of social media users with a critical perspective. The results of the study found that the delivery of social criticism through YouTube animated content about rising fuel prices was carried out by using animation as a character that tells the criticism of the video maker, then the storyline is easily understood by the audience, the video content is made in a comedic or joking manner, and the language used can be understood by the audience.